An Overview on Abdominal Wound Dehiscence - Adly Salem Oda, Mennat Allah Oda; Ebrahim Khalil , Alaa Mohammed; Tantawy , Ismail; Kasem, Hesham Mohamed; Shreef , Khalid (Journal of Neonatal Surgery, 2025)
Abdominal wound dehiscence is one of the most serious postoperative complications following abdominal surgery, associated with high morbidity, prolonged hospitalization, increased healthcare costs, and a mortality rate that can reach up to 45%. It represents a partial or complete disruption of a laparotomy wound closure, leading to separation of fascial layers and, in severe cases, evisceration. The incidence ranges between 0.4% and 3% of abdominal surgeries and is influenced by patient factors, surgical technique, and postoperative care. Early diagnosis, preventive measures, and timely management are crucial to reducing adverse outcomes